ILLEGAL MIGRATION-CONCEPTUAL DELIMITATIONS - CRISTINA FLORINA POPESCU (PANAIT) (Challenges of the Knowledge Society)
Illegal migration is a mobile phenomenon, which ignores national borders, a threat that originates outside the community and extends to Western societies. This phenomenon is becoming larger and irregular migrants are often in a precarious situation and exposed to the criminals involved in various manifestations of organized crime. The future risk factors of the illegal migration are the demographic bomb, because the population is decreasing in European countries and increasing rapidly in poorer countries, droughts, floods, deforestation, that cause conflicts between climate refugees , extreme poverty, totalitarian regimes, epidemics, can trigger millions of people, the elderly and the working population imbalance which leads to the permanent import of immigrants To combat this phenomenon, states must engage and cooperate with each other. Measures taken by states must balance their integration policy for immigrants, legally residents and asylum policy to comply with international conventions. Also, states must adopt anti-immigrant policies, consisting of subordination visa policy to the interests of international security and exchange of information and, not least, to continue the Schengen process, as a value of humanitarian law applied in the field. The aim of the research is to characterize this dangerous phenomenon for the society and the goal is to identify strategies to combat illegal migration.